1987
DOI: 10.1080/00268978700100551
|View full text |Cite
|
Sign up to set email alerts
|

Electronic interaction in trimeric mixed valence clusters

Abstract: The theory of double exchange is generalized to mixed valence (MV) trinuclear clusters. The results obtained by quantum-theoretical calculations of exchange and resonance splittings are compared to the results of the model theory which takes account of Heisenberg and double exchange. The comparison demonstrates unambiguously the coincidence of transfer parameters and the model double exchange parameters. The double exchange parameters of trinuclear MV clusters depend on total and intermediate spins as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…100 K), a double exchange (p = À1816.39 AE 0.43 cm À1 ) interaction slightly reduced isotropic Heisenberg-type exchange interaction (À81.48 AE 0.02 cm À1 ) because of the electronic delocalization effect. [21] The energy level plot ( Figures S12-S13) indicated that the delocalized state 1 has the same antiferromagnetic ground state (S T = 2) as its localized state, compatible with previous conclusions. [22] The energy level gap between ground state (S T = 2) and the first excited state S T = 1) is 37.12 cm À1 at zero field.…”
Section: Angewandte Chemiesupporting
confidence: 88%
See 1 more Smart Citation
“…100 K), a double exchange (p = À1816.39 AE 0.43 cm À1 ) interaction slightly reduced isotropic Heisenberg-type exchange interaction (À81.48 AE 0.02 cm À1 ) because of the electronic delocalization effect. [21] The energy level plot ( Figures S12-S13) indicated that the delocalized state 1 has the same antiferromagnetic ground state (S T = 2) as its localized state, compatible with previous conclusions. [22] The energy level gap between ground state (S T = 2) and the first excited state S T = 1) is 37.12 cm À1 at zero field.…”
Section: Angewandte Chemiesupporting
confidence: 88%
“…Thus, the double exchange interaction cannot completely suppress antiferromagnetic Heisenberg-type ordering, and 1 still exhibits spin-frustration. [21] To investigate the effect of the electron-hopping property on magnetoelectric property of the trinuclear iron, constraint density function theory (CDFT) calculations with and without applied electric field were performed using CP2K program. [23] For charge-frustration, two different states, including (Fe1 III , Fe2 III , Fe3 II ) and (Fe1 II , Fe2 III , Fe3 III ), were involved.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Electron transfer theory has been further developed in Refs. [6][7][8][9][10][11][12][13]. A detailed discussion of the state of the double exchange theory can be found in a number of monographs and ample overviews [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…One can see that these clusters are quite different from the MV dimmers in which the double exchange always stabilizes the ferromagnetic ground state. 4 On the other hand these systems are similar to triangular MV trimmers, [27][28][29] tetrahedral MV tetramers, [30][31][32] and hexanuclear octahedral d 2 25d 1 clusters 33 exhibiting transfer frustration that seems to be a common feature of all MV clusters with symmetric triangular faces (for a more detailed discussion see ref.…”
Section: [62p]dmentioning
confidence: 99%